The Functioning of Cross-Border Marketplaces on The Example Of Polenmarkt Hohenwutzen in Osinów Dolny - Paweł CZAPLIŃSKI (Communications of International Proceedings, 2021)
Frontier marketplace trade, as a special form of trade, has accompanied mankind for centuries. It still plays an important pro-development role, particularly important for local spatial systems where broadly understood endogenous resources are limited.  The main aim of the study was to characterize the market in Osinów Dolny, located in the Polish-German border area, with particular emphasis on its impact on local development, i.e. the commune of Cedynia. The analyses and syntheses were based on the results of direct research (survey research and participant observation) conducted in 2019-2020 at the Polenmarkt Hohenwutzen marketplace. They show that the spatial range of the marketplace's influence on the German side goes far beyond the local scale and is based on relatively constant relations. Modernization of the marketplace, which improve physical mobility not only in the trade zone, but also its facilities, especially for the elderly, as well as equipping the stands with new IT technologies, which, apart from the information function, are to facilitate non-cash transactions, are to be a panacea for the declining attractiveness of this form of retail trade organization. All the presented results and the conclusions drawn from it were made before the declaration of the global pandemic, therefore the presented text does not contain detailed references to this phenomenon.
Keywords: Marketplace Trade; Osinów Dolny; Frontier Zone; Marketplace